Mitigating mismatch power losses in photovoltaic systems under partial shading: a comparative study of series-parallel and alternative configurations - Othman, Raghad Adeeb; Al-Yozbaky, Omar Sharaf Al-Deen Yehya; Alabbawi, Ali Abbawi Mohammed (Institute of Advanced Engineering and Science, 2025)
Utilizing the photovoltaic effect, photovoltaic (PV) systems are a popular technique for capturing solar energy and turning sunlight into electricity. However, environmental factors, especially shade, significantly impact photovoltaic system efficiency. Shadows cast on PV panels by surrounding structures, trees, accumulated dirt, clouds, and debris can seriously impair their performance. The purpose of this study was to investigate how shade affects photovoltaic systems utilized in residential settings. Series-parallel (SP) topology for PV system have been investigated. Additionally, in this work, a PV system of 5 kW of the residence home has been proposed and multi cases of shading examined. Through the results obtained when partial shading was applied, it was found that the highest efficiency of the system was when partial shading irradiance (Ir = 500 W/m2) was applied to one column (5 modules) as 82.84%, while the worst and least equipped case was when the shading was applied to the corners and random shading at (8 modules), where the efficiency decreased to approximately 39.24% and 40.64% respectively.